Perubahan Minat Masyarakat Desa Terhadap Mata Pencaharian Di Kota - Mustofa, Shofyan; Maulida, Tsalitsa; Faristiana, Andhita Risko (Jurnal Sosiologi Pertanian dan Agribisnis, 2024)
Changes in the livelihood interests of rural communities to urban areas have become an important topic in the field of sociology and economics. This study aims to analyze the factors that influence changes in the livelihood interests of rural communities to urban areas. The research method used is observation, interviews, documentation. The results of the study show that the factors that influence the change in the livelihood interests of rural communities to cities are economic, social and psychological factors. Economic factors include better job opportunities, higher salaries, and opportunities to increase economic well-being. Social factors include the influence of friends and family already working in cities, as well as the desire to pursue an urban lifestyle. Psychological factors include the desire to seek new experiences and challenges in life. This study concludes that changes in rural community interest in livelihoods in the city are driven by a variety of complex factors. Rural communities must be provided with adequate education and training in order to compete in cities. In addition, the government must create enough jobs in rural areas to reduce migration to cities and strengthen the local economy.